Poverty Reduction with Strategic Communication : Moving from Awareness Raising to Sustained Citizen Participation - Mozammel, Masud (World Bank, Washington, DC, 2017)
The role of communication in Poverty Reduction Strategy (PRS) processes has evolved since 2000. The introduction of new communication channels for public policy debate has empowered a wide array of stakeholders who previously were absent or marginal in the development agenda. Initially, consultations were mainly a donor-led requirement, often done to access Heavily Indebted Poor Country (HIPC) funding quickly. This experience led to the recognition that more can be gained by working in partnership with other stakeholders. This publication updates a 2005 review of communication in PRSs. It includes four country case studies (Ghana, Tanzania, Moldova, and Nepal) and a regional analysis of Latin America and the Caribbean. It explores how the use of strategic communication has expanded beyond the PRS and is now being integrated into national development planning and implementation. Many of these strategies are shifting their focus from a 'dissemination and publicity strategy' to a 'communication program' that emphasizes information intervention beyond the traditional campaign, workshop or seminars. Compared with the 2005 review, the main difference is the institutionalization of communication, moving beyond the one-time experience for the first set of PRSs to broader, deeper sustained communication in support of poverty reduction and national development strategies. A second major difference is expanding beyond communication and participation in PRS formulation to PRS implementation, monitoring, and evaluation. The challenges of communication in national development strategies both within and between government, civil society, and donors correspond to some of the key challenges of the PRS initiative, how to create a genuinely participatory, and comprehensive process. Donor harmonization and aid coordination have improved government-donor relations, but both parties need to forge a new relationship with civil society for the more ambitious agenda to promote good governance.